2015
DOI: 10.1186/s13104-015-1231-8
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral anticancer chemotherapy: What influences patients’ over or non-adherence? Analysis of the OCTO study through quantitative–qualitative methods

Abstract: BackgroundNumerous oral anticancer chemotherapies are available. Non-adherence or over-adherence to these chemotherapies can lead to lowered efficacy and increased risk of adverse events. The objective of this study was to identify patients’ adherence profiles using a qualitative–quantitative method.MethodsA capecitabine treatment was initiated for 38 patients with advanced breast or colorectal cancer. At inclusion, information on patients’ beliefs was reported using a questionnaire. Later, Information on pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
14
2
2
Order By: Relevance
“… 20 We are therefore not able to expand the literature on this issue of increasing relevance. 20 22 Finally, future studies may also benefit from measuring changes of patients’ perceptions and adherence over time, as we only adopted a cross-sectional design. Longitudinal studies may reveal significant associations at certain timepoints, ie, at the beginning of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 We are therefore not able to expand the literature on this issue of increasing relevance. 20 22 Finally, future studies may also benefit from measuring changes of patients’ perceptions and adherence over time, as we only adopted a cross-sectional design. Longitudinal studies may reveal significant associations at certain timepoints, ie, at the beginning of treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 8 19 Even less is known about the risk of over-adherence in patients receiving capecitabine. 20 22 Although the numbers generally appear to be satisfying, even a small variation of adherence may result in adverse clinical consequences. 14 , 20 23 …”
Section: Introductionmentioning
confidence: 99%
“…25 Bourmaud et al have shown that patients treated with oral anticancer therapies are asking for tailored educational interventions, driven by their healthcare providers. 26 It is therefore an opportunity to put the patient back at the heart of care, in the institution, by modifying professional Thought software and returning to a symmetrical care-care relationship. Everyone will be able to recognize and take advantage of the expertise of the other: the expert patient in his or her construction, based on his or her experiences and experience; the expert caregiver in his or her care-taking practice.…”
Section: Discussionmentioning
confidence: 99%
“…She searches the scientific literature and discovers several studies using electronic monitoring systems to assess adherence to oral chemotherapy regimens and hormonal therapy for breast cancer [2628]. The monitors are expensive, but Dr. Jones determines that the cost is justified – there is a high correlation between electronic monitoring adherence estimates and clinical outcomes for many conditions.…”
Section: Case Study 1: Academic Researchermentioning
confidence: 99%